15.7k views
2 votes
Given h(x)=-x+5h, solve for x when h(x)=0.

Given h(x)=-x+5h, solve for x when h(x)=0.-example-1
User Jpihl
by
5.3k points

2 Answers

4 votes

Answer:

5

Explanation:

Set h(x) to zero then solve:

0 = -x + 5

-5 = -x

5 = x

User Zi
by
5.3k points
3 votes

Answer:

x = 5

General Formulas and Concepts:

Pre-Alg

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define

h(x) = -x + 5

h(x) = 0

Step 2: Solve

  1. Substitute: 0 = -x + 5
  2. Isolate x term: -5 = -x
  3. Isolate x: 5 = x
  4. Rewrite: x = 5
User Markpirvine
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.